(3QhVI GdWGdHjf hYeOI GdeaJjfs - (3jMji Hf TQa Hf oepqQj Hf MSf GdMRGej GdMhQGfj, Gdfhhj, GdTGaYqj, CHh RcQjG, eMjj GdOjf,J (B676 (3g` s ((3efjI QOjf HGdTQbjI (B/ (3eUQ s)
(3ChdgG (B:s
(3eSJhQ GdChd , HOGjI hGajI (B:" (3ahLgGf CMOgeG dGjLhR GdQei EPG de jcf VQH GdcaGQ EdG HVQ GdeSde dCf ZGjJg Cf fNGa Ydi CfaSfG , hOe GdeSde s
(3BNQgG (B:s
(3aQY (B:(3EPG ChdO LGQjJg GdeMQeI Ydjg HfSH ChQVGY Ch eUGgQI dReg MO ai bhd , hGdJYRjR Ydi GdCTgQ bGd GdEeGe GdQGaYi bO JjSQ GdaQGZ ef gPG GdcJGH ai Pi GdbYOI SfI KdGK YTQI hSJeGFI bGd eUfaI QMeg Gddg aQZJ efg jhe GdCMO NGeS YTQ TgQ QHjY GdChds
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B149 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B202s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B2003s
Keywords: (3Gdabg GdESdGejs